Resting-state brain activity predicts selective attention deficits during hyperthermia exposure. (1st January 2020) - Qian, Shaowen; Yan, Sumei; Zhou, Chang; Shi, Zhiyue; Wang, Zhaoqun; Xiong, Ying; Zhou, Yi
Abstract: Purpose: Environmental hyperthermia exerts detrimental effect on attention performance that might increase the probability of accidents for high risk occupation. Previously, we reported aberrant activations and selective attention deficits under task performing during hyperthermia. However, whether resting-state baseline during hyperthermia would contribute to the reported selective attention deficits remains unclear. Materials and methods: Here, we investigated the resting-state activity within two attention subsystems named dorsal attention network (DAN) and ventral attention network (VAN) using the conjoint analysis of functional connectivity (FC) and regional cerebral blood flow (CBF). Blood oxygenation level dependent (BOLD) and 3 D arterial spin labeling data were obtained from 25 healthy male participants under two simulated thermal conditions: normothermic (25 °C for 1 h) and hyperthermic condition (50 °C for 1 h). Results: Paired comparisons on the FC and CBF showed decreased activity in the bilateral frontal eye field (FEF) and intraparietal sulcus (IPS) in the DAN but increased activity in the ventral frontal cortex (VFC) in the VAN. The CBF-FC correlation analysis further confirmed decreased CBF-FC coupling in the bilateral FEF in the DAN and increased coupling in the VFC in the VAN. Additionally, the left IPS and FEF in the DAN showed altered CBF per unit functional connectivity in the CBF/FC ratio analysis. Multiple regression analysis revealed that the selectively altered performances were predicted by alterations of the multiple metrics within the DAN and VAN. Conclusions: These findings suggested that altered resting-state brain activity within the attention networks might provide potential neural basis of the selective deficits for different cognitive-demand attention tasks under hyperthermia.